It's all a matter of balanced tensions : Irish medical missionaries in Nigeria, 1937-1967 - Veale, Ailish Ellen (Trinity College (Dublin, Ireland). Department of History, 2015)
Prior to 1936 Catholic nuns were forbidden by canon law from practising medicine or midwifery, as these were deemed a threat to their vows of chastity and obedience. Only after a lengthy campaign of propaganda and action by a number of pioneer women doctors, and male and female religious, was this canon law rule amended. The Medical Missionaries of Mary is an Irish congregation of medical and nursing nuns, founded in 1936 by Mother Mary Martin directly after the reversal of this canon law ban.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin